Analisis dan Perancangan Sistem Informasi Akuntansi Penjualan Jasa Desain - Cristian, Lianawati; Winarto, Winarto; Sonny, Sonny; Fernando, Edith (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The purpose of this paper is to analyze problems in CV TVB and to create sales system of design service in credit to the company. The method used is analysis and design method. The analysis method is observation, interview, literature study; meanwhile, the design method is using object-oriented. The expected result is this paper will be useful for the company in increasing affectivity and efficiency in design service cycle, and also as the reference for other researchers to research the same problem. The conclusion is that the computerized sales system design service from the purchasing order process until printing report will solve problems in the old system and procedure.